(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
The article analyzes current trends in the development of entrepreneurship in the construction industry and related services. The study was conducted in the context of key modern processes: urbanization, digitalization, and the transition to a sustainable economy. The paper analyzes the main challenges faced by the industry, such as rising resource costs, personnel shortages, and the need to implement green technologies and digital project management tools.